Eccentric connectivity index of composite graphs - Došlić, Tomislav; Saheli, Mahboubeh (Utilitas Mathematica, 2014)
We present explicit formulas for the values of eccentric connectivity index for several families of composite graphs. The results are applied to some graphs of chemical interest, such as C4 nanotubes and nanotori.